2011
DOI: 10.1021/pr200685r
|View full text |Cite|
|
Sign up to set email alerts
|

Integration of Metabolomics and Expression of Glycerol-3-phosphate Acyltransferase (GPAM) in Breast Cancer—Link to Patient Survival, Hormone Receptor Status, and Metabolic Profiling

Abstract: Changes in lipid metabolism are an important but not well-characterized hallmark of cancer. On the basis of our recent findings of lipidomic changes in breast cancer, we investigated glycerol-3-phosphate acyltransferase (GPAM), a key enzyme in the lipid biosynthesis of triacylglycerols and phospholipids. GPAM protein expression was evaluated and linked to metabolomic and lipidomic profiles in a cohort of human breast carcinomas. In addition, GPAM mRNA expression was analyzed using the GeneSapiens in silico tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 41 publications
2
52
0
1
Order By: Relevance
“…In breast cancer, higher GPAM expression was associated with longer MFS or DFS in two cohorts for at least one probe set (GSE9195: HR ¼ 0.36, P ¼ 0.044; GSE42568: HR ¼ 0.67-0.73, P ¼ 0.016-0.019), supporting previous findings (23). Conversely, when the analysis was performed stratified according to ER and HER2 status, GPAM was found to be associated with shorter MFS or DFS in HER2-positive patient subsets in two cohorts (GSE19615: HR ¼ 2.62, P ¼ 0.040; GSE21653: HR ¼ 1.46, P ¼ 0.040; Supplementary Table S9).…”
Section: Gpam Expression In Human Cancerssupporting
confidence: 86%
“…In breast cancer, higher GPAM expression was associated with longer MFS or DFS in two cohorts for at least one probe set (GSE9195: HR ¼ 0.36, P ¼ 0.044; GSE42568: HR ¼ 0.67-0.73, P ¼ 0.016-0.019), supporting previous findings (23). Conversely, when the analysis was performed stratified according to ER and HER2 status, GPAM was found to be associated with shorter MFS or DFS in HER2-positive patient subsets in two cohorts (GSE19615: HR ¼ 2.62, P ¼ 0.040; GSE21653: HR ¼ 1.46, P ¼ 0.040; Supplementary Table S9).…”
Section: Gpam Expression In Human Cancerssupporting
confidence: 86%
“…Although the precise role of aberrant lipid biosynthesis is unknown, several studies have shown that the lipid profile has been linked to survival, ER status, and tumor grade in human breast cancer (7,8). The lipid composition of tumors is also affected by dynamic processes, having been observed to vary with cell proliferation, apoptosis, and necrosis (9).…”
Section: Introductionmentioning
confidence: 99%
“…Conditions of the mass spectrometer were as above but with a run time of 18 min. For liver lipidomics, the protocol was adapted in part from a published method ( 29 ). Accurately weighed liver samples ( ‫ف‬ 50 mg) were homogenized in water-methanol (43:57 v/v) in a Precellys ® 24 bead homogenizer (Bertin Corp., Rockville, MD).…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%